Which Factors?. (17th October 2018) - Hou, Kewei; Mo, Haitao; Xue, Chen; Zhang, Lu
Abstract: Many recently proposed, seemingly different factor models are closely related. In spanning tests, the q -factor model largely subsumes the Fama–French five- and six-factor models, and the q 5 model subsumes the Stambaugh–Yuan four-factor model. Their "mispricing" factors are sensitive to the construction procedure, and once replicated via the traditional approach, are close to the q -factors, with correlations of 0.8 and 0.84. Finally, consistent with the investment CAPM, valuation theory predicts a positive relation between the expected investment and the expected return.